Estudio del mecanismo de ensamblado de las nucleocápsides virales en partículas infecciosas de arenavirus: disección molecular de la interacción entre la nucleoproteína NP y la proteína Z - Armella Sierra, Alicia Beatriz (2022)
The Junin arenavirus (JUNV) genome encodes the nucleoprotein (NP), the envelope glycoproteins precursor (GPC), the L RNA polymerase, and the Z matrix protein. NP is organized into two globular domains, separated by a flexible linker. Z comprises a central RING domain flanked by the N- and C-terminal mobile arms.\nBased on the information obtained for other arenaviruses, indicating that Z-NP interaction is necessary for the incorporation of the nucleocapsids into virions, we aimed to: 1) analyze the interaction between JUNV NP and Z proteins, both in vitro and in cellulo systems 2) elucidate the Z residues involved in this interaction and 3) examine the enzymatic activity of the C-terminal domain (CTD) of NP. To this, Z, fused to Maltose Binding Protein, and the CTD domain of NP (NPctd) were expressed in bacterial expression systems and further purified. The interaction between both proteins was analyzed in vitro by agarose gel retardation and pulldown assays. Alongside, immunoprecipitation experiments were performed to evaluate Z-N interaction in mammalian cells. Results suggest that NPctd interacts with Z, and that hydrophobic residues located within the C-terminal arm of Z are involved in this interaction. Furthermore, we found that NPctd displays ribonuclease activity, not previously reported for JUNV.